Innovations and barriers in sustainable and green finance for advancing sustainable development goals - Raman, Raghu; Ray, Suparna; Das, Dayana; Nedungadi, Prema (Frontiers in Environmental Science, 2025)
This study employs a mixed-methods approach to investigate the role of sustainable and green finance in advancing UN sustainable development goals (SDGs). We use quantitative bibliometric methods with machine learning-based BERTopic modeling and case study analysis to reveal trends. This study presents a cocitation analysis of the SDGs to visualize the interconnectedness between goals, highlighting the central role of SDG 13 (climate action) and key linkages with SDGs related to economic growth (SDG 8), industry and infrastructure (SDG 9), clean energy (SDG 7), and environmental sustainability (SDGs 6, 15). The findings indicate that innovations such as green fintech, social impact bonds, and risk models are crucial for facilitating renewable investment and mitigating environmental impacts. The identified barriers include high transaction costs and insufficient institutional frameworks in developing countries, hindering the broader adoption of green finance tools. Case studies from South Africa, Brazil, and other developing nations have examined the implementation of green bonds and loans. They highlight significant efforts by stakeholders to use these financial instruments to support SDGs, particularly SDG 7, SDG 13, and SDG 17 (partnerships). However, challenges such as nascent regulatory environments, market barriers, and capacity constraints persist, inhibiting mainstream integration. Key research avenues include quantifying investment needs, tailoring financial instruments, and developing derisking mechanisms to foster cross-sector coordination and international partnerships. The study underscores the necessity of innovative and inclusive financial mechanisms to mobilize capital flows aligned with the priorities of the Global South. Future research directions include the development of advanced data analytics, adaptation to local contexts, technological integration, and exploration of the social dimensions of sustainable finance. This study provides actionable insights for policymakers, financial institutions, and researchers, emphasizing the crucial role of sustainable finance in driving global sustainability.